2012
DOI: 10.1093/infdis/jis254
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pan-Resistant Bacteria With Antibodies to a Broadly Conserved Surface Polysaccharide Expressed During Infection

Abstract: Our findings raise potential new therapeutic options against PNAG-producing bacteria, including even pan-resistant pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 30 publications
(49 reference statements)
0
41
0
1
Order By: Relevance
“…While previous studies have shown that bacterial capsules can be effective immunogens, this is the first set of data to our knowledge that supports the potential use of the capsular polysaccharide as a target for antibody-mediated therapeutics in A. baumannii. Additional targets which may also be useful include OmpA (23) and the noncapsular bacterial surface polysaccharide poly-␤-(1-6)-N-acetylglucosamine (52).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have shown that bacterial capsules can be effective immunogens, this is the first set of data to our knowledge that supports the potential use of the capsular polysaccharide as a target for antibody-mediated therapeutics in A. baumannii. Additional targets which may also be useful include OmpA (23) and the noncapsular bacterial surface polysaccharide poly-␤-(1-6)-N-acetylglucosamine (52).…”
Section: Discussionmentioning
confidence: 99%
“…The RNDs play a major role in the intrinsic multidrug resistance phenotypes of both A. baumannii and P. aeruginosa (6,19,20). To test our hypothesis that intrinsic and acquired antibiotic resistance enhances fitness during infection, in other clinically relevant organisms, we assessed the fitness of Tn insertions in the A1S_1649 and A1S_1801 genes prepared in a highly virulent A. baumannii strain AB5075 (21) using a murine model of lethality after intraperitoneal challenge (22). As expected, mutations in both genes led to increased susceptibility to antibiotics, with the MIC for tobramycin decreasing from 48 mg/liter for AB5075 wild type to 12 and 16 mg/liter for AB5075 with Tn insertions in homologs of A1S_1649 and A1S_1801, respectively.…”
Section: Fitness Cost Of Antibiotic Susceptibility In Other Pathogenimentioning
confidence: 99%
“…In Acinetobacter baumannii , deletion of the pga locus led to loss of the biofilm phenotype, which was restored by complementation [23]. Similar findings were found with Burkholderia cepacia complex (BCC) [24], K. pneumoniae [25], and Bordetella pertussis [26]. Recently, PNAG’s role in biofilm formation was reported in Bacillus subtilis [27], the first Gram-positive bacillus found to produce PNAG.…”
Section: Biology Of Pnagmentioning
confidence: 68%
“…The presence of pga genes is not enough, by itself, to firmly establish that the PNAG molecule is synthesized and expressed. Nonetheless, it is notable that, to date, essentially all the investigations finding pga genes in a microbe’s chromosome were able to confirm the presence of PNAG at the bacterial surface[6,2224,26,33,34]. Interestingly, the introduction of the pga locus into a PNAG-negative bacteria can lead to the production of PNAG [27].…”
Section: Genetics and Biosynthesis Of Pnagmentioning
confidence: 99%